2011
DOI: 10.1111/j.1551-2916.2011.04703.x
|View full text |Cite
|
Sign up to set email alerts
|

Carbothermal Reduction and Nitridation of Titanium Dioxide in a H2–N2 Gas Mixture

Abstract: This article examines carbothermal reduction/nitridation of rutile in a H2–N2 gas mixture in the temperature‐programmed and isothermal experiments in a fixed‐bed reactor. The aim of this investigation was to establish the reduction/nitridation sequence, the reaction degree, and the rate of synthesis of titanium oxycarbonitride under different experimental conditions. The off‐gas composition was monitored using an infrared sensor (CO, CO2, and CH4) and a dew point analyzer (H2O). Extents of reduction and nitrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 15 publications
0
24
1
Order By: Relevance
“…Conversion of TiO 2 to titanium oxycarbonitride followed the path of conversion of rutile presented elsewhere [9,10]. Reduction of iron oxide to metallic iron and conversion of titania to titanium oxycabonitride in the H 2 -N 2 gas mixture was faster than in nitrogen.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Conversion of TiO 2 to titanium oxycarbonitride followed the path of conversion of rutile presented elsewhere [9,10]. Reduction of iron oxide to metallic iron and conversion of titania to titanium oxycabonitride in the H 2 -N 2 gas mixture was faster than in nitrogen.…”
Section: Discussionmentioning
confidence: 93%
“…Reduction of ilmenites started with conversion of pseudorutile into ilmenite which was further reduced to titania and metallic iron [6]. Further reduction of titania followed the same sequence as pure rutile [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] It was shown that gas atmosphere had a significant effect on the rate of reaction. Conversion of rutile to titanium oxycarbonitride occurred at lower temperature and higher rate in comparison with production of oxycarbide.…”
Section: Introductionmentioning
confidence: 99%
“…Conversion of rutile to titanium oxycarbonitride occurred at lower temperature and higher rate in comparison with production of oxycarbide. 10,11) This stimulates a further study of synthesis of titanium oxycarbonitride from ilmenites.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation